An Instructional Design for Online Learning in Vocational Education according to a Self-Regulated Learning Framework for Problem Solving during the CoViD-19 Crisis - Sangsawang, Thosporn (Universitas Pendidikan Indonesia, 2020)
This study used multimedia games as instruments for critical thinking activities based on the Self-Regulated Learning (SRL) framework for the CoViD-19 crisis, supported by achievement tests and questionnaires. The results showed that the present method is effecttive to improve students' learning achievement, confirmed by the higher posttest results compared to than those of the pretest. The educational goals of SRL theories were developed through student-directed instructional design online where the students' guide made some input into their learning processes. The students' satisfaction in learning with the SRL framework for the CoViD-19 crisis gained a high level, informing that the SRL framework for problem solving during the CoViD-19 crisis was useful for teaching and career training. Teaching styles (such as the stable focus, orientation, or intent) constituted the entire patterns of teaching behaviors. This study implies that a self-directed learner can be described as being self-managing in a situation where the individual is engaged in student-centered instructions.